Energy-saving and IAQ control in hospital patient room by bed-integrated ventilation - Wang, Zhiqi; Bivolarova, Mariya; Melikov, Arsen (CLIMA 2022 conference, 2022)
The annual energy-saving potential and IAQ improvement by use of a hospital bed-integrated pollution source control, a ventilated mattress (VM) and local bed ventilation (LBV), was studied. The VM is designed to capture in the bed and exhaust human body bio-effluents. The LBV is supplies clean air close to the breathing zone of the patient in bed and exhausts the polluted (might be infected) exhaled air from the patient before it is mixed with the room air. Exhaled air removal efficiency of the LBV were assumed at 40%, 60% and 80%. Thus, the risk of cross-infection was reduced. Energy use simulations were performed by IDA-ICE software. Intake fraction was used to indirectly assess the risk of cross-infection. Three scenarios were simulated to evaluate the energy-saving potential of the source control methods: 1) a double-patient room (none of patients is infected) using the VM and constant air volume ventilation (CAV), 2) a double-patient room (either one or two patients is infected) using the VM and CAV and 3) a double-patient room (either one or two patients is infected) using the VM, the LBV and CAV. The results reveal that using the VM and the LBV at decreased background ventilation rate can be an effective method for reducing the energy costs needed for hospital wards. Depending on the operation of the VM and the LBV, the energy-saving was between 1880 kWh and 67964 kWh. The annual energy-saving was up to 83.6% when the ward with two infected patients using LBV at 80% exhaled air removal efficiency and CAV at a reduced ventilation rate, compared with the reference cases of only CAV operating at 12 air changes per hour (ACH).